Genetic and Phenotypic parameters of growth, reproductive and survival performance of Horro sheep at Bako Agricultural Research Center - Solomon A.; Gemeda, D. (Bako Agricultural Research Center, 2000)
Data collected on a flock of Horro sheep at Bako research center (1978 to 1997) have been analyzed for phenotypic performance on growth and reproductive performance and mortality. Additionally genetic analyses were done to estimate genetic parameters (heritability, and genetic and phenotypic correlations) for early growth traits and litter size. Genetic and environmental trends were estimated for the total period along with quantifying the level and effect of inbreeding. Analysis on monthly weights to the age 55 month was also done. Least square mean values for birth weight (BW), weaning weight (WW), six month weight (6MW) and yearling weight (YRW) were 2.71, 11.81, 15.36, and 24.0 kg, respectively. Year of birth, sex, rearing type (birth type for BW) were found to affect all of these early growth traits while dam age within parity affected all but 6MW. Age at weighing was a significant (P<0.05) source of variation for WW, 6MW and YW. Mortality to 30, 90, 180 and 365 days of age was significantly affected (P<0.05 to P<0.001) by sex, type and year of birth, dam age and birth weight. Year of birth and birth weight have also significant effect on mortality to 3 and 7 days of age. Predicted probabilities of survival to 3, 7, 30, 90, 180, and 365 days were 96, 95, 92, 80, 66 and 56%, respectively. Conception and lambing were significantly affected by year of mating and weight, age and parity of the ewe. Overall predicted probabilities of conception and lambing were 77 and 75%. Year of birth and sex were found to have significant effect on monthly weights to the age of 55 months. Direct heritability estimates under a sire and three different animal models were in the range of 0.18 to 0.32, 0.10 to 0.26, 0.16 to 0.26, and 0.23 to 0.31 for BW, WW, 6MW, and YW, respectively. Maternal heritability estimates for the four traits ranged from 0.08 to 0.24. Genetic correlations between BW, WW, 6MW, and YW were in the range of 0.31 to 0.98 while phenotypic correlations were 0.21 to 0.73. The overall average inbreeding coefficient was 0.78 % with about 32% of animals being inbred. No significant (P>0.05) effect of inbreeding was detected though the effect approached significance level (P=0.088) for YW. Genetic trends for BW, WW, 6MW and YW had shown an annual increase of 6, 44, 56, and 94.g. Environmental trends have shown higher decline than the genetic gain resulting in significant decline in phenotypic performance. Heritability of litter size ranged from 0.06 to 0.17 under different models. Medium heritability of early growth traits indicates genetic improvement can be realized through selection for these traits. Concurrent improvement in the environmental (management) factors should be made. Low heritability for litter size implies increase in this trait can be achieved mainly through management (e.g. increasing ewe weight).